2002
DOI: 10.1101/gad.995802
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian cell size is controlled by mTOR and its downstream targets S6K1 and 4EBP1/eIF4E

Abstract: The coordinated action of cell cycle progression and cell growth (an increase in cell size and cell mass) is critical for sustained cellular proliferation, yet the biochemical signals that control cell growth are poorly defined, particularly in mammalian systems. We find that cell growth and cell cycle progression are separable processes in mammalian cells and that growth to appropriate cell size requires mTOR-and PI3K-dependent signals. Expression of a rapamycin-resistant mutant of mTOR rescues the reduced ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

63
802
6
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 957 publications
(895 citation statements)
references
References 69 publications
63
802
6
5
Order By: Relevance
“…Transgenic T cells described here were also found to have increased rates of glycolysis, consistent with in vitro observations that Akt can promote increased nutrient uptake and glycolysis [35,42]. The mechanism of this increased resting T cell size is uncertain, but the PI3 K/Akt pathway has been shown to play an important role in cell size regulation in other cell types [43][44][45]. In addition, the Akt-induced increase in glucose metabo-lism can contribute to increased cell size directly by promoting the generation of metabolic substrates for biosynthesis, cell growth, and maintenance of increased biomass.…”
Section: Discussionsupporting
confidence: 84%
“…Transgenic T cells described here were also found to have increased rates of glycolysis, consistent with in vitro observations that Akt can promote increased nutrient uptake and glycolysis [35,42]. The mechanism of this increased resting T cell size is uncertain, but the PI3 K/Akt pathway has been shown to play an important role in cell size regulation in other cell types [43][44][45]. In addition, the Akt-induced increase in glucose metabo-lism can contribute to increased cell size directly by promoting the generation of metabolic substrates for biosynthesis, cell growth, and maintenance of increased biomass.…”
Section: Discussionsupporting
confidence: 84%
“…Complete AKT activation depends on phosphoinositide-dependent kinase-1 4 (PDK1) and mTORC2, which phosphorylate AKT at two key sites: the activation loop (T308) and the C-terminal hydrophobic motif (S473), respectively (10,11). mTOR signaling is regulated through a network of feedback loops, protein partners, substrates, and regulators (12,13). Among them, PRAS40 (proline-rich AKT substrate 40 kDa) is a key regulator of mTORC1.…”
Section: Introductionmentioning
confidence: 99%
“…mTORC1 phosphorylates the hydrophobic motif of p70S6K on T389 (17). On the other hand, phosphorylation of 4E-BP1 at S65 by mTORC1 prevents the binding of 4E-BP1 to the eIF4E translation initiation factor activating capdependent translation (13).…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian target of rapamycin (mTOR), a 289 kDa Ser/Thr kinase, lies downstream of phosphatidylinositol 3 0 -kinase (PI3K), and senses mitogenic stimuli, nutrient conditions (Hara et al, 2002;Kim et al, 2002) and ATP (Dennis et al, 2001), and regulates multiple cellular events required for cellular growth (size) and proliferation (Fingar et al, 2002;Martin and Hall, 2005), differentiation (Erbay and Chen, 2001;Shu et al, 2002), and survival (Hosoi et al, 1999;Beuvink et al, 2005). Dysregulation of PI3K-mTOR pathway generates a favorable oncogenic environment and has been seen in a variety of transformed cells and human tumors, including rhabdomyosarcoma, lung, bladder, renal, ovary, breast, prostate, gastric, pancreatic, head and neck carcinomas, lymphoma, melanoma, glioma and other brain malignancies (Huang and Houghton, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The data indicate that rapamycin is a potent inhibitor not only for cell proliferation, growth, and survival but also for cell motility. Studies have demonstrated that rapamycin inhibits proliferation and growth (size) by suppression of mTOR-mediated S6K1 and 4E-BP1/eIF4E pathways (Fingar et al, 2002;Bjornsti and Houghton, 2004;Fingar et al, 2004), induces apoptosis of cells through downregulation of mTOR-mediated 4E-BP1/eIF4E pathway , and inhibits differentiation of C2C12 cells in an mTOR-kinase activity-independent manner (Erbay and Chen, 2001), despite existence of controversy (Shu et al, 2002). However, the underlying mechanism of rapamycin inhibition of cell motility remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%